HUBUNGAN PENGGUNAAN KB SUNTIK 1 BULAN DAN 3 BULAN DENGAN GANGGUAN POLA HAID DI PUSKESMAS GULAI BANCAH KECAMATAN MANDIANGIN KOTO SELAYAN BUKITTINGGI - Nazirun, Novia (Ensiklopedia Sosial Review, 2019)
Expanding family planning contraceptives in Indonesia there are hormonal and non-hormonal long-term One of the tools that hormonal contraception KB injecting 1 month (estrogen/progesterone) and 3 months (progesterone). Based on the initial survey that the researcher did on August 1, 2013 in Health Center Stew Bancah by interviewing 10 respondents who use contraception 1 month experience menstrual disorders by 2 people and 10 respondents who use contraception injections 3 months experience menstrual disorders by 9 people . The goal is to determine whether there is a relationship KB injecting 1 month and 3 months with menstrual disorders . This study is a cross sectional analytic. This research was carried out from June to November 2013, with a sample 68 respondents, which consisted of 31 respondents Injectable 1 month and 37 respondents Injectable 3 months. The data was collected using a questionnaire and univariate and bivariate data using chi square test. The results of the study , the use of the type of family planning injection occurred 1 month menstrual disorders by 10 respondents (33.3 %) of the 31 respondents , while the use of the type of family planning injection occurred 3 months of menstrual disorders by 22 ( 59.5 % ) of the 37 respondents. From the research, there is a relationship injectable contraceptive use 3 months to disruption of menstrual patterns in the sub-district health centers Bancah Stew Mandiangin Koto Selayan Bukittinggi 2013. It is expected that this study can be input to conduct further research on the factors that can cause menstrual disorders and advice to family planning acceptors injection to dig menembah insight and knowledge of existing information.